Research on the rehabilitation intervention of Taijiquan on adolescent anxiety - Zhang, Yi; Xie, Shuyu (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: Anxiety is a psychological process that is influenced by multiple factors. Its core component is the expectation of the uncertainty of the interaction with a specific situation, which is a typical negative emotion. Anxiety disorder is a clinical term. Epidemiological studies have shown that anxiety disorder is the most popular psychiatric problem in adolescents, and adolescence is a prone period for anxiety in adolescents. During this period, the individual’s development and physical and mental changes are at a turning point. With the emergence of secondary sexual characteristics, individuals will be curious and at a loss about their body, physical, and psychological changes. At this time, due to internal and external changes. The lack of a transformation mechanism will cause great harm to children’s study life, interpersonal communication, etc. In recent years, domestic experts and scholars have gradually deepened their research on this issue, and their understanding of the disease mechanism has become more and more comprehensive. New treatment methods and treatments Means continue to emerge, further improving the efficacy. However, the overall treatment effect of adolescent anxiety in medical clinic is still not satisfactory, and it is still one of the difficulties in treatment. my country has a large population base and a large number of youth groups. The healthy growth of young people is critical to the future of the country. This study intends to focus on the psychological disorders, sleep disorders, and physical disorders of adolescent anxiety caused by psychological and physical changes in the normal growth process. Make use of various exercises in Chen-style Taijiquan to selectively formulate non-destructive treatment and rehabilitation programs and standards, and evaluate its rehabilitation value, so that it can get a good recovery, and prevent the sequelae caused by drug treatment intervention, which can cause damage Students speed up their escape from the trouble of illness, resume normal academic progress and communication as soon as possible, and even improve the quality of life. Methods: From 2015 to 2020, the Guangdong Xiaowu Taijiquan Club successively accepted a total of more than 300 young Taijiquan students. It was found that 28 adolescent anxiety patients chose Taijiquan for rehabilitation intervention. They are all males, ranging in age from 11 to 17 years old. Most of them come from middle schools in Guangzhou and scholars who leave home due to illness. Based on this, based on the medical history and symptoms, as well as the confirmed data from the hospital, it can be known that among the 28 adolescents with anxiety symptoms, 3 had severe anxiety, 7 had moderate anxiety, and 18 had mild anxiety. Combining the traditional Chinese medicine meridian theory, the Yellow Emperor’s Internal Classic, etc. in the Taijiquan series of exercises and martial arts and confrontation, the main selections are Tai Chi Zhan Zhuang, Que Dilong, Shaking Big Rod, Refining Qi, Chen Style Tai Chi Spring and Autumn Broadsword and Competitive Tai Chi Push Hands Training, And learn the existing Taijiquan theory. According to different situations, different exercises and exercise amounts are used, with three months as the first time point to observe the effect of exercise, and then check the rehabilitation effect in six months and one year. Results: (1) From the perspective of traditional Chinese medicine meridians, it can be found that boys’ adolescent anxiety is mainly due to the need for a large amount of kidney essence and yin and blood support during puberty, but it is caused by sexual fantasies, masturbation and other problems formed by men’s changes in women and physiological changes. The contradiction caused by the insufficient demand is greater than the supply, and this indirectly reflects psychological and ideological anxiety, which affects the source of the spleen and stomach, especially the hot and humid climate in the south has a great relationship with the adolescent’s spleen and stomach. Make this contradiction more difficult to resolve. (2) With this as an entry point, in the first stage, firstly cultivate vitality to relieve negative emotions and restore the lost yang energy once a day for 1-2 hours; second, learn the basic skills of Tai Chi The dragon and the big pole shake, the Qidilong can exercise the strength of the lower limbs through the left and right ups and downs and the internal breathing adjustment method, which is in line with the effect of the upper and lower circulation of the meridian in traditional Chinese medicine, so that the turbid qi decreases and the clear qi rises. And the big rod shakes by twisting the towel spirally, repeatedly rubbing the Laogong acupoint on the palms of both hands, after training, it makes people feel soothing. At the same time, the rotation of the waist and hips can also stimulate the spleen and stomach movement. Third, after each exercise, you need to refine the Qi, and do two sets for 15 minutes each time. It can turn the essence into vitality, and restore the essence and invigorate the brain. (3) The second stage is mainly to learn Chen-style Taijiquan Spring and Autumn Broadsword and competitive Taiji Push Hands, each practice 15 times, push hands for 5 minutes, push 3 rounds. Practice can increase concentration, transfer negative emotions, and increase communication. At the same time of the above learning, there will be one or two boxing learning lessons per week and accept the baptism of traditional culture. Three months of uninterrupted Taijiquan practice, mild and moderate, and one severe patient achieved good recovery results. The remaining two severe patients recovered completely after half a year without sequelae, and returned to normal study and life a year later. Conclusion: The recovery of various levels of adolescent anxiety can be carried out through Tai Chi internal exercises, which can delight the body and mind and stabilize emotions, relieve negative emotions, achieve yin and yang balance, and promote symptom recovery. The amount of Tai Chi exercise can be large or small, so pay attention to step by step. Choose the right amount to prevent the aggravation of negative emotions caused by rushing, and to avoid the decline in physical fitness caused by the increase in drugs. At the same time, Tai Chi exercise can transform male students’ adolescent masturbation, sexual fantasies and other problems, achieve the effects of nourishing kidney essence, strengthening the body, dredging the meridians, and regulating the function of the internal environment. Therefore, we choose an experienced Tai Chi rehabilitation teacher, and believe that the rehabilitation teacher’s reasonable and scientific selection and arrangement of exercises, through reasonable and correct exercises, can well help the impaired students to accelerate their escape from anxiety and return to normal learning and life as soon as possible. Communicating. And Tai Chi is a systemic exercise, with equal emphasis on body muscle movement and meridian and consciousness. Pay attention to national traditional culture, traditional Chinese medicine theory and boxing theory learning, combine theory with practice, get rid of blind pursuit of Western psychotherapy, choose Tai Chi exercise with its own national characteristics, and work hard for the physical and mental health of adolescent students. The quality and cultural self-confidence of the entire nation is of great significance.